2011
DOI: 10.5352/jls.2011.21.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Red Garlic Extract for Anti-Obesity and Hypolipidemic in Obese Rats Induced High Fat Diet

Abstract: This study tested the anti-obesity and hypolipidemic effects of red garlic extract in obese rats induced by a high fat diet over a period of 4 weeks. Red garlic extract of 15 brix was added in 1, 3, 5 and 7% ratios in diets. The obesity index and body fat content significantly decreased in rats fed a diet with over 3% red garlic extract compared to the control group. There was no significant difference in weight of visceral and epididymal fat in rats fed red garlic extract. Total lipid and triglyceride levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
1
0
3
Order By: Relevance
“…Since lard samples naturally contain Chol, the increased lard consumption might exceed a range of the compensatory reduction of hepatic endogenous lipid synthesis in HF-fed rats. A previous study [34] in which ingredients in the AIN-93G-based control diet and HF diet are almost the same as those in the present study shows that the HF diet consumption for 4 weeks decreases serum HDL-Chol level and increased LDL-Chol in rats. Given that LDL takes up Chol from the liver whereas HDL carries blood Chol to the liver, the changes in HDL and LDL would not contribute to the hepatic lipid accumulation in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Since lard samples naturally contain Chol, the increased lard consumption might exceed a range of the compensatory reduction of hepatic endogenous lipid synthesis in HF-fed rats. A previous study [34] in which ingredients in the AIN-93G-based control diet and HF diet are almost the same as those in the present study shows that the HF diet consumption for 4 weeks decreases serum HDL-Chol level and increased LDL-Chol in rats. Given that LDL takes up Chol from the liver whereas HDL carries blood Chol to the liver, the changes in HDL and LDL would not contribute to the hepatic lipid accumulation in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…The consumption of fructose has now become a lifestyle, increasing the incidence of obesity and associated complications (Fakhoury-Sayegh et al , 2015), but not only fructose, Emamat et al ’s (2019) result has shown that galactose intake was significantly associated with higher risk of NAFLD. Diet modification and weight loss are considered important components of NAFLD treatment (Lee et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…홍마늘 분말의 체 내 지질저하 효과는 고지방 식이에 의한 비만 유도 흰쥐에서 흑마늘 분말과 비슷한 결과를 보였으며 [19], 15 brix의 홍마늘 열수추출물을 3∼7% 첨가급이 시 체지방량 감소 및 체내 지질 배설효과가 있다는 연구가 보고되어 있다 [24].…”
Section: 서 론unclassified
“…본 연구는 항산화 활성 및 체내 지질 개선에 효과가 있는 것으로 보고 [19,24,25] [3][4][5][6] Refer to the Values in a column sharing the same superscript letter are not significantly different at p<0.05.…”
Section: 서 론unclassified
See 1 more Smart Citation